A Robust Strategy Based on Marine Predators Algorithm for Large Scale Photovoltaic Array Reconfiguration to Mitigate the Partial Shading Effect on the Performance of PV System - Yousri D.; Babu T.S.; Beshr E.; Eteiba M.B.; Allam D. (Institute of Electrical and Electronics Engineers Inc., 2023)
Particle swarm optimization (PSO); Photovoltaic effects; Solar power generation; Algorithm performance; Comprehensive comparisons; Partial shading effects; Particle swarm optimizers; Photovoltaic arrays; Population-based algorithm; Weighted objective function; Wilcoxon signed rank test; Photovoltaic cells